Determinants of The Quality of Financial Reporting Audit Quality as an Intervening Variable : Study on Regional State-Owned Bank Associations Banten - Sari, Gema Ika; Widyastuti, Tri; Daito, Apollo; Rachbini, Widarto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The quality of audits carried out by internal auditors has not met expectations in implementing risk management control so it is not optimal in supporting the quality of financial reporting that can present information with relevance, reliability, testability, and neutrality. The purpose of this study was to analyze the determinants of the financial reports' quality with audit quality as an intervening variable in Bank BUMN Tbk. The research method used is quantitative research with a quantitative descriptive approach. The research population is the internal auditors of Bank BUMN Banten Province totaling 227 auditors. The technique of distributing questionnaires using Google Forms so that 205 respondents were obtained, the rest did not respond. The sampling technique uses a saturated sample of all internal auditors as a sample. Data analysis used SEM (Structural Equation Model Analysis) analysis with PLS (Partial Least Square). The results of the study had a direct effect: auditor independence and ethics had a positive and significant direct effect on the quality of financial reporting. This verification is the mental attitude of the internal banking auditors who are independent of pressure in formulating opinions due to professional responsibility in auditing standards and prioritizing independence in appearance in the interpretation of the audit implementation to maintain an unbiased attitude in the assessment of Bank Banten financial statements. The support of the banking auditor's internal ethics to maintain confidentiality has a positive effect in supporting the quality of financial reporting due to the function of the internal auditor in carrying out the task of examining, evaluating, and monitoring the adequacy and effectiveness of internal controls in the operation of Bank BUMN as seen from the internal auditors' efforts to take action. care and protect information. Through mediation, the audit quality that is formed from the auditor's competence will have a positive effect on the relevance of the quality of financial reporting so that the implementation of audit quality in banking becomes the right method to support the quality of banking financial reporting.